Intolerance to uncertainty, the tendency to experience worry and pessimism as factors in the relationship between emotional dependence and violence - Momeñe López, Janire; Estevez, Ana; Pérez-García, Ana María; Maguregi, Andere (Anales de Psicología / Annals of Psychology, 2022)
People with emotional dependence present constant concerns about possible abandonment or betrayal by their partner. In this way, they implement a wide range of retention strategies aimed at covering the great need for control in the relationship. In addition, they feel dissatisfaction and frustration in the relationship since they feel they will never get what they want or expect from it. Therefore, the objectives of the study are aimed at analyzing the possible relationship between emotional dependence, intolerance to uncertainty, tendency to worry and pessimism. Also, the mediating role of these factors in the relationship between emotional dependence and permanence in violent relationships is verified due to the high prevalence of occurring jointly in the same relationship. A total of 258 people participated, 77.1% women and 22.9% men with ages ranging from 18 to 67 (M = 32.63; SD = 11.66). The results reflected positive relationships between emotional dependence, intolerance to uncertainty, tendency to worry and pessimism. Likewise, it is proven that emotional dependence leads to permanence in violent relationships through the factors mentioned.